2022
DOI: 10.1073/pnas.2117899119
|View full text |Cite
|
Sign up to set email alerts
|

Composition-dependent ordering transformations in Pt–Fe nanoalloys

Abstract: Significance Dynamically understanding the microscopic processes governing ordering transformations has rarely been attained. The situation becomes even more challenging for nanoscale alloys, where the significantly increased surface-area-to-volume ratio not only opens up a variety of additional freedoms to initiate an ordering transformation but also allows for kinetic interplay between the surface and bulk due to their close proximity. We provide direct evidence of the microscopic processes control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 48 publications
0
32
1
Order By: Relevance
“…This impedes morphology preservation during the thermal treatment due to the lack of capping ligands or protecting templates to stabilize the high surface energy atoms at the high annealing temperature, leading to nano-polyhedra or nanospheres after the intermetallic conversion [ 112 , 115 , 116 ]. For example, the surface evolution and composition-dependent ordering transformation processes of Pt–Fe NCbs have been in situ observed on the single-particle level using electron microscopy [ 117 ]. During vacuum annealing, this ordering occurs via either “surface nucleation and growth” or “interface” mechanism, resulting in a core–shell configuration.…”
Section: General Synthetic Strategies For Pt-based Nanocrystalsmentioning
confidence: 99%
“…This impedes morphology preservation during the thermal treatment due to the lack of capping ligands or protecting templates to stabilize the high surface energy atoms at the high annealing temperature, leading to nano-polyhedra or nanospheres after the intermetallic conversion [ 112 , 115 , 116 ]. For example, the surface evolution and composition-dependent ordering transformation processes of Pt–Fe NCbs have been in situ observed on the single-particle level using electron microscopy [ 117 ]. During vacuum annealing, this ordering occurs via either “surface nucleation and growth” or “interface” mechanism, resulting in a core–shell configuration.…”
Section: General Synthetic Strategies For Pt-based Nanocrystalsmentioning
confidence: 99%
“…The mechanism of the synthesis of intermetallic compounds has been studied using in situ techniques. 38 For instance, the phase transition of cubic Pt 3 Co nanocrystals from a solid solution to an intermetallic phase via high temperature annealing was investigated using in situ scanning transmission electron microscopy. 39 The results showed that two mechanisms of phase transition exist, resulting in a layer by layer ordering of atomic arrangements from the surface to interior.…”
Section: Dalton Transactions Communicationmentioning
confidence: 99%
“…[ 6–8 ] One of the most promising but challenging strategies is directly tracking the atoms’ location and configuration during the dynamic evolution, which now can be achieved by the transmission electron microscopy (TEM) associated with the recent emerging in situ holders. [ 9–13 ] That is, the fast and delicate variation of the reaction interface during variable driving stimuli can be captured in real‐time at an atomic level.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] One of the most promising but challenging strategies is directly tracking the atoms' location and configuration during the dynamic evolution, which now can be achieved by the transmission electron microscopy (TEM) associated with the recent emerging in situ holders. [9][10][11][12][13] That is, the fast and delicate variation of the reaction interface during variable driving stimuli can be captured in real-time at an atomic level. Remarkable in situ TEM investigations have been applied in probing the structural evolution of reactants in solid-gas reactions, such as the oxidation of metal nanostructures, reduction of metal oxides, reconstruction of metallic particles during catalytic reactions, etc.…”
Section: Introductionmentioning
confidence: 99%